Longevity records of citril finches Carduelis citrinella: analysing 43 years of continuous ringing - A. Borràs; J. Cabrera; T. Cabrera; X. Colomé; J. C. Senar (Arxius de Miscel-lània Zoològica)
Longevity records (maximum lifespan) of free-ranging birds are basic to understand the evolution of avian senescence patterns. Here we provide minimum longevity records for the citril finch Carduelis citrinella, an endemic cardueline finch of high mountains in Central and Western Europe. Continuous ringing over 43 years in the Eastern Pyrenees allowed recording of a male of seven years and seven months, a female of six years and three months old, and 60 individuals of more than three years of age. There was no difference in the sex ratio between individuals of more than three years of age. These values agree with the potential natural longevity of the species computed from previously recorded mortality rates of the species.